Vigne Nuove, Corviale, Laurentino 38, three utopias created in Rome - Anna Rita Emili (IJRDO - Journal of Social Science and Humanities Research, 2019)
The article compares three major settlements to explain how the city of Rome developed during the seventies. This was a period in which Italian politics was capable of governing the country. It set precise procedures to develop town planning and supported an archetypal, architectural project, featuring large, utopian dimensions. In fact, a series of very unusual districts were constructed during those years and this article compares three of them: Corviale, Vigne Nuove and Laurentino 38. The comparison reveals certain links between them, such as the partial or total use of béton brut; they are all considered as large, intensive constructions; the relationship created between the walkways, the accommodation and the communal spaces. However, these aspects are developed and applied differently within each of the three districts. After an analysis of the political and historic mood of the period in which the three districts were constructed, the article tackles the relationship between these settlements by comparing not only their urban planning and architectural design, but also the details and use of the typical material of the time, such as béton brut. Politics has always been a fundamental ingredient of utopia. It began with Plato’s ideal Republic, the essence of which was imbued with ethics and justice epitomising the constitution and structure of the city. In 1516, Thomas More coined the term in his Utopia, in which he criticised the monarchy in favour of a democracy based on equality without the social hierarchy found in reality. Thus, Utopia has, from its origins,represented democratic politics, with a vision of a future open to new solutions. Italian architecture has expressed and portrayed these values since the end of the nineteen sixties, and has been considered to be an expedient capable of testifying to a profoundly democratic, innovative, political and cultural moment in time. This research is a part of the scope based theme of residence, ranging from temporary housing to major urban projects.